The effect of different rise time on partial discharge activity of inter‐turn insulation under square wave voltage. (9th May 2012) - Zhou, K.; Tao, X. T.; Huang, Y. C.; Li, X. T.; Zhao, W.
SUMMARY: Partial discharge (PD) activity of the inter‐turn insulation of electric motor winding is investigated under different rise time of the square wave voltage, and the superposition effect of the polarized charges on PD activity is also analyzed for the specimen. Under different rise time of the square wave, tests of the PD activity (e.g., PD inception voltage (PDIV) and phase resolved PD (PRPD) pattern) and the thermal stimulated depolarization current are both performed. Comparing the results of the PRPD patterns at different rise time of the square wave, most of PD moves to the zero point of square wave voltage with the reduction in rise time. Also, PDIV decreases with the reduction in rise time. Through the analysis of a complete polarization process at the square wave voltage, the superposition effect of the polarized charges leads to the enhancement of electric field in the specimen when the polarity of square wave voltage rapidly reverses. With the reduction in rise time at square wave, more polarized charges can not follow changes of the applied voltage since the relaxation time of these dipoles is longer than the rise time of square wave, which leads to the enhancement of the electric field across a cavity. For this reason, they result in the reduction in PDIV and the movement of PRPD patterns to zero point of square wave voltage. Copyright © 2012 John Wiley & Sons, Ltd.